Catching the ASEAN wave - Lim, Teo Lay
Bordered by powerhouses China and India, Southeast Asia is sometimes overlooked by multinational companies. But ignoring the transformation now under way could blind leaders to this increasingly attractive market-and to the arrival of some bold new innovations on the global stage.
Keywords: ASEAN; Business model